Patient with Marfan Syndrome and a Novel Variant in FBN1 Presenting with Bilateral Popliteal Artery Aneurysm. (29th March 2018) - Mohammad, Ahmed; Helmi, Haytham; Atwal, Paldeep S.
Abstract : We present a 43-year-old man with aortic root dilation, mitral valve prolapse, and marfanoid appearance, who presented with acute onset left leg pain. He underwent a Doppler ultrasound that revealed left popliteal artery aneurysm with thrombus. CT angiogram showed bilateral popliteal artery aneurysms. After repairing of his left popliteal artery aneurysm, he was sent for genetic evaluation. He was diagnosed with Marfan syndrome (MFS) based on the revised Ghent criteria and then underwent FBN1 sequencing and deletion/duplication analysis, which detected a novel pathogenic variant in gene FBN1, denoted by c.5872 T>A (p.Cys1958Ser). MFS is a connective tissue disorder with an autosomal dominant inheritance due to pathogenic variants in FBN1 that encodes Fibrillin-1, a major element of the extracellular matrix, and connective tissue throughout the body. MFS involves multiple systems, most commonly the cardiovascular, musculoskeletal, and visual systems. In our case we present a rare finding of bilateral popliteal artery aneurysms in a male patient with MFS.